Edukasi tentang Stroke dan Hipertensi pada Usia Muda di Desa Simasom Dusun 3 (Batu Lanja) - Pane, Mustika Dewi; Rambe, Muhammad Arsyad Elfiqah (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2023)
Young age is the age in the 26-45 year category. Age in this category is already at risk for disease if individuals do not maintain their diet and health. Some diseases that can attack individuals in this age category are stroke and hypertension. The purpose of this activity is expected to increase public knowledge about stroke and hypertension. This activity is carried out on adolescents aged 26-45 years. The method used is lectures using power point slides that contain material and also brochures. The material provided is the definition of stroke, signs of stroke symptoms, stroke management, definition of hypertension, signs of symptoms of hypertension, and treatment of hypertension. The results obtained after conducting health education showed that the majority of people understood the definition of stroke, signs of stroke symptoms, stroke management, definition of hypertension, signs of symptoms of hypertension, and treatment of hypertension. which has been given. Suggestions for further activities are conducting health education about drugs, cigarettes, reproductive health, mental health, and family planning. For health workers to pay more attention to problems that often affect the community, and improve health education with the aim of increasing public knowledge and awareness